Perbandingan Fikih Syafi'iyah dengan UU Tindak Pidana Kekerasan Seksual Terkait Perlindungan Hukum Perempuan - Syaerozi, Ahmad (Alif Lam : Journal of Islamic Studies and Humanities, 2024)
This research is driven by the disparities in the eradication of violence against women as outlined in Law Number 12 of 2022, which pertains to Criminal Acts of Sexual Violence (UU-TPKS), and the teachings of Imam Syafi'i. The research methodology employed is library research, utilizing primary and secondary sources as data sources. Primary data is derived from scholarly sources that are directly relevant to the central topic, such as articles, newspapers, books, and scientific journals. Secondary data refers to additional data that complements and supports primary data. After conducting extensive investigation, the author discovered many findings: Law no. 12 of 2022 was enacted to safeguard the rights of those who have experienced sexual violence, as such crimes frequently manifest in society as physical, psychological, and sexual abuse. In addition to overseeing the enforcement of criminal penalties, such as monetary fines. Furthermore, Imam Syafi'i strongly highlighted that Islamic law unequivocally forbids any and all manifestations of sexual aggression. According to Shafi'i scholars, sexual assault can be penalized with Qishash, diyat, and ta'zir, depending on the specific offense